Selenium-enriched bacterial protein as a source of organic selenium in broiler chickens - Mohamed Abd Alla, Dalia Abd Alla (2018)
Selenium (Se) is an essential dietary trace mineral associated with several important roles in the biological processes. Livestock are routinely supplemented with various Se sources and many studies have indicated that organic Se is more efficient and bioavailable than inorganic sodium selenite (SS). Some bacterial strains have the ability to produce organic selenium biologically through selenite microbial reduction and accumulate it in their cells as Se-containing proteins. The possibility of using bacterial organic Se as a feed supplement may provide an interesting source of organic Se for animals and also humans through the food chain. Hence, this study aimed to identify a potential new product of bacterial organic Se and show the possibility of using it in animals’ feed to improve animals’ Se status and antioxidant status. In the first experiment of this study, four isolates, identified as Enterobacter cloacae (ADS1, ADS7, ADS11), and Klebsiella pneumoniae (ADS2) from rumen fluid origin, and one isolate from hot spring water (Stenotrophomonas maltophilia (ADS18), were able to transform 47.17- 62.52% of the absorbed inorganic Se into organic form (Secontaining proteins). Organic Se-containing proteins in all the selected strains showed in vitro antioxidant properties, therefore, these strains may offer a potential source of organic Se due to their Se-tolerant nature and higher biomass organic to inorganic Se ratio. The second experiment examined the influence of bacterial organic Se on growth performance, meat quality and meat antioxidant, immunity and selenoproteins gene expression in broiler chickens. A total of 180, day-old, broiler chicks were randomly assigned to 5 groups: T1, basal diet; T2; basal diet + 0.3 mg/kg SS; T3, basal diet + 0.3 mg/kg ADS1-Se; T4, basal diet + 0.3 mg/kg ADS2-Se; T5; basal diet + 0.3 mg/kg ADS18-Se. Different sources of bacterial Se or SS, increased the birds’ survival rate, serum and tissues antioxidants and Se accumulation, improved meat’s water holding capacity, and up-regulated some selenoproteins mRNA. Birds fed bacterial Se-protein showed high intestinal villus height, better Se retention with higher tissues Se deposition, better anti-oxidative capacity and meat tenderness with lower serum and tissues TBARS level more than SS. Selenium of ADS18 had a superior action in improving Se retention, antioxidant system and expression of selenoproteins compared to ADS1 and ADS2 bacterial Se. The third experiment examined the effects of the combination of Vit E with bacterial organic Se and inorganic Se on growth performance, meat quality, immunity and antioxidant status of broiler chickens. A total of 216, day-old chicks were randomly assigned to six dietary treatments: T1, basal diet; T2, basal diet + 100 mg/kg α- tocopherol acetate; T3, Basal diet + 0.3 mg/Kg SS; T4, Basal diet + 0.3 mg /kg ADS18-Se; T5, Basal diet + 0.3 mg /kg SS+ 100 mg/kg α-tocopherol acetate; T6, 0.3 mg/kg ADS18-Se + 100 mg/kg α-tocopherol acetate. Supplementation of ADS18-Se in broiler chickens improved the performance, antioxidant system, meat quality, ceacum microbiota, and immunity response more than SS. Moreover, adding of 100 mg/kg of Vit E to the diet resulted in better performance, meat quality, and meat fatty acid modulation, with no effect on ceacum microbial population. The synergistic effect of Se and Vit E appear clearly in the performance, antioxidant system, and immunity response. The supplementation of Vit E alone had a better effect on most of the antioxidant and immunity parameters than the combination with Se, while the combination with bacterial organic Se had better effect than the combination with SS. Moreover, the inclusion of 100 mg/kg Vit E with 0.3 mg/kg ADS18-Se, effectively could support performance, antioxidant system, and immunity more than using ADS18-Se alone, while no difference between using SS alone or combined with Vit E. In conclusion, sodium selenite and bacterial organic Se of ADS1, ADS2, and ADS18 could enhance broiler biological activities, however, bacterial organic sources were more efficient, and can be used to produce Se-enriched meat. Moreover, inclusion of Vit E with bacterial organic Se could improve it’s efficiency.